Implementasi Pemberdayaan Ekonomi Berbasis Green Economy Masyarakat Melalui Program Bank Sampah Mawar Desa Marengan Daya Dalam Perspektif Maqashid Syariah - Febby Ayu Ainiyah; Dahruji Dahruji; Mashudi Mashudi (JURNAL RISET MANAJEMEN (JURMA), 2023)
Economic empowerment is one way to improve people's lives. The "Mawar Waste Bank" program is a community initiative established by the residents of Marengan Daya village, utilizing various types of waste through various management methods to generate income for the community. The goal of this empowerment system based on the green economy, from the perspective of Maqashid Sharia, is to understand how the community implements this program with values aligned with Maqashid Sharia. The majority of the community, who are Muslim, must balance seeking worldly benefits and their hereafter, including applying Maqashid Sharia values in their daily lives. The research conducted is qualitative and descriptive in nature, with the subjects being members of the community participating in the Mawar Waste Bank program. The results of this study indicate that the community implementing the waste bank program can generate income from waste management, creating economic value. Additionally, they can participate in various savings programs provided by waste management entities, effectively investing their resources. Regarding Maqashid Sharia, the community diligently applies the values encompassing hifdz ad-din, hifdz nafs, hifdz aql, hifdz nasl, and hifdz maal.